Pengaruh Disiplin Kerja, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dinas Parekrafbudpora Gresik - Wijayanto, Kevin Julian (Jurnal Ilmiah Poli Bisnis, 2022)
Abstract The background of this research is the performance of employees of the Gresik Office of Tourism and Culture who have not reached the agency's target. The purpose of this study is to analyze whether there is a partial influence of discipline, motivation, and work environment on performance. The method in this study uses quantitative methods. The data analysis technique in this study used multiple linear regression analysis. The number of samples used in this study were 71 respondents. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For test aids using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that discipline has a significant effect on employee performance, work motivation has a significant effect on employee performance, and work environment has a significant effect on employee performance.